2018
DOI: 10.3390/jfb9040069
|View full text |Cite
|
Sign up to set email alerts
|

Development of Phosphatized Calcium Carbonate Biominerals as Bioactive Bone Graft Substitute Materials, Part I: Incorporation of Magnesium and Strontium Ions

Abstract: Synthetic materials based on calcium phosphate (CaP) are frequently used as bone graft substitutes when natural bone grafts are not available or not suitable. Chemical similarity to bone guarantees the biocompatibility of synthetic CaP materials, whereas macroporosity enables their integration into the natural bone tissue. To restore optimum mechanical performance after the grafting procedure, gradual resorption of CaP implants and simultaneous replacement by natural bone is desirable. Mg and Sr ions released … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 78 publications
(89 reference statements)
0
15
0
1
Order By: Relevance
“…in our previous study, mouse mesenchymal stem cells (MMScs) were cultured in Mg-containing hydroxyapatite (Mg-Ha) solution for 72 h. The reverse transcription-quantitative Pcr (rT-qPcr) results demonstrated that the mrna expression levels of alP, osx and runx2 in the Mg-Ha group were significantly higher compared with MMSCs cultured without Mg-Ha, suggesting that Mg-Ha promoted MMSc osteogenic differentiation (5). To meet clinical requirements, several bone-related ions were added to synthetic Ha to improve its effects, which indicated that Mg-Ha was suitable for clinical application (6). Magnesium and hydroxyapatite composites can overcome the shortcomings of traditional bioceramics, including lack of bone formation inducing ability (7).…”
Section: Introductionmentioning
confidence: 99%
“…in our previous study, mouse mesenchymal stem cells (MMScs) were cultured in Mg-containing hydroxyapatite (Mg-Ha) solution for 72 h. The reverse transcription-quantitative Pcr (rT-qPcr) results demonstrated that the mrna expression levels of alP, osx and runx2 in the Mg-Ha group were significantly higher compared with MMSCs cultured without Mg-Ha, suggesting that Mg-Ha promoted MMSc osteogenic differentiation (5). To meet clinical requirements, several bone-related ions were added to synthetic Ha to improve its effects, which indicated that Mg-Ha was suitable for clinical application (6). Magnesium and hydroxyapatite composites can overcome the shortcomings of traditional bioceramics, including lack of bone formation inducing ability (7).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 This triggered a smaller series of detailed investigation on the formation mechanisms and on the exploitation of coralline calcium carbonate for biomedical applications. [17][18][19][20][21][22][23] These contributions evidenced that coralline calcium carbonate is a potential bone lling material with good osteoconductivity. 20,[24][25][26][27] However, the use of biogenic and thus pre-formed porous ceramic matrices comes at a price which made this general approach less attractive: they typically pose problems due to their meager mechanical integrity and loadbearing capabilities which arise due to their ungovernable porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Natural CaCO 3 of a porous framework from coral can also be a source of apatite. For example, Sethmann et al [9] prepared macroporous apatite ceramics via a hydrothermal treatment of aragonite coral skeletons. Fujita et al investigated the factors influencing the conversion of lithium calcium borate glass to HAp in dilute K 2 HPO 4 solutions [10].…”
Section: Introductionmentioning
confidence: 99%